Efficacy and Tolerability of Darunavir/Ritonavir in Combination with Abacavir/Lamivudine: An Option in Selected HIV-Infected Patients. Issue 5 (September 2013) - de los Santos, Ignacio; Gómez-Berrocal, Ana; Valencia, Eulalia; Asensi, Victor; Gijón, Paloma; Moreno, Victoria; Vergas, Jorge; Bernardino, Ignacio
Abstract : Objective: To evaluate the safety and efficacy of abacavir/lamivudine (ABC/3TC) plus darunavir/ritonavir (DRV-RTV) in experienced patients.Methods: The study was conducted in Spain in 6 hospital clinics and involved HIV-positive patients who needed to change their antiretroviral treatment (ART) for several reasons. They started fixed-dose combination (FDC) ABC/3TC (600 mg/300 mg), DRV (400 mg 2 tablets qd), and RTV (100 mg) from January 2010 to April 2012. The patients were evaluated at baseline and at intervals of 3 to 6 months, and at least once at the end of the follow-up. Adverse events (AEs), concurrent medications, HIV-associated conditions, and adherence were also assessed at each visit.Results: Seventy-six patients were included from 6 sites (60 male). Median CD4 cell count was 479/mm 3, and the median time on follow-up was 10.1 months. Thirty-eight patients (50%) have reached 48 weeks of follow-up and 32 (84.2 %) have achieved HIV RNA <50 copies/mL in this period. Immunological recovery was observed with a median CD4 count increase of 119 cells/mm 3 by week 48. There were no patients who discontinued the study treatment due to AEs, and all the toxicities that lead to change ART at baseline were resolved or improved substantially.Conclusion: This study showed that the study regimen provided consistent antiviral and immunological responses until 48 weeks. The antiretroviral effect of the regimen was observed in subsets of patients evaluated, including those with high baseline HIV-1 RNA levels and virological failure and those with switching, with little or no difference across subgroups.